2022
DOI: 10.1073/pnas.2117988119
|View full text |Cite
|
Sign up to set email alerts
|

TGFB2-AS1 inhibits triple-negative breast cancer progression via interaction with SMARCA4 and regulating its targetsTGFB2andSOX2

Abstract: Triple-negative breast cancer (TNBC) is the most challenging breast cancer subtype for its high rates of relapse, great metastatic potential, and short overall survival. How cancer cells acquire metastatic potency through the conversion of noncancer stem-like cells into cancer cells with stem-cell properties is poorly understood. Here, we identified the long noncoding RNA (lncRNA) TGFB2-AS1 as an important regulator of the reversibility and plasticity of noncancer stem cell populations in TNBC. We revealed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 59 publications
0
21
1
Order By: Relevance
“…In addition, a recent study reported that SMARCA4 interacts with lncRNA TGFB2-AS1 and regulates the transcription of its target genes. 38 We next asked whether SMARCA4 involves the effect of PSMB8-AS1 on VCAM1 and ICAM1 expression. However, RNA pulldown assays revealed no interaction between PSMB8-AS1 and SMARCA4 (Figure S20A).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a recent study reported that SMARCA4 interacts with lncRNA TGFB2-AS1 and regulates the transcription of its target genes. 38 We next asked whether SMARCA4 involves the effect of PSMB8-AS1 on VCAM1 and ICAM1 expression. However, RNA pulldown assays revealed no interaction between PSMB8-AS1 and SMARCA4 (Figure S20A).…”
Section: Resultsmentioning
confidence: 99%
“…CD44 + CD24 − cells with stem cell-like features are the most common cell type in breast cancer, 49 which is associated with tumor recurrence, metastasis and drug resistance. 50 The CD44 antigen is a multifunctional transmembrane glycoprotein associated with cell adhesion, activation, migration and differentiation and is considered a promising tumor marker.…”
Section: Resultsmentioning
confidence: 99%
“…48 These findings supported the notion that the camouflaging RBCm coating on these nanoparticles can reduce self-recognition and clearance by the RES and prolong their half-life in circulation in vivo. 42 3.4 In vitro cytotoxicity of HR@UCNPs/CpG-Apt/DOX CD44 + CD24 − cells with stem cell-like features are the most common cell type in breast cancer, 49 which is associated with tumor recurrence, metastasis and drug resistance. 50 The CD44 antigen is a multifunctional transmembrane glycoprotein associated with cell adhesion, activation, migration and differentiation and is considered a promising tumor marker.…”
Section: Biocompatibility and Immune Escape Of Hr-ucadmentioning
confidence: 99%
“…SOX-2 has demonstrated the potential to be a clinically useful biomarker to maintain lung CSCs [ 33 ]. There are also studies in the literature reporting that SOX-2 is overexpressed and acts as an oncogene in lung cancer [ 68 , 69 ]. Although the role of SOX-2 in lung cancer has been determined as a result of clinical and preclinical studies [ 70 ].…”
Section: Discussionmentioning
confidence: 99%